The influence of local environmental and socio-economic conditions on the impacts of ash storms - Forte, Pablo; Dominguez, Lucia; Bonadonna, Constanza; Lamberti, Maria Clara; Gregg, Chris E.; Bran, Donaldo Eduardo; Castro, Jonathan M. (2018)
Volcanic ash wind-induced remobilization events have increasingly been reported in different areas around the worl during the last decades